Combined family-based association and linkage analyses in families affected by attention-deficit hyperactivity disorder - Cristina M. Justice; Kwangmi Ahn; Benjamin Jung; Luke J. Norman; Gustavo Sudre; Wendy Sharp; Marine Bouyssi-Kobar; Saadia Choudhury; Stevi Gligorovic; Paul Kundzicz; Maria T. Acosta; Philip Shaw (Human Genetics, 2026)
Attention deficit hyperactivity disorder (ADHD) is one of the most prevalent and heritable of neurodevelopmental disorders. To characterize the genetic variants contributing to this heritability, we studied families with members affected by ADHD. Genome-wide array data were obtained on two cohorts: NHGRI Family Cohort (359 nuclear families,1538 individuals) and NCR Family Cohort (25 multigenerational and 132 nuclear families, 631 members). A meta-analysis of family-based association tests (FBAT) of the two cohorts identified three genome-wide significant associations, one upstream from TFRC , and two that were intronic to GSDME and to TRIM31 , with the last gene previously implicated in ADHD. Genes associated with ADHD (MAGMA, gene-based association P < 0.05) overlapped with genes implicated in ADHD by prior case/control genome-wide association studies. Meta-analyses of the linkage signals identified one significant linkage region (LOD > 3) on 19p13.2-13.11 that encompassed a genome-wide significant variant in the FBAT of the NHGRI Family Cohort (rs55741253, P = 2.68 × 10 − 8 ). Additionally, two of the five linkage regions that reached a LOD > 2 in our meta-analysis replicated significant linkages from prior studies (prior studies reporting 13 linkages with LOD > 3.0; hypergeometric test of overlapping linkage signals, P < 0.01). Using neuroimaging data from the NCR cohort, we found genes associated with ADHD overlapped with genes associated with the brain’s total surface area and a feature of functional connectivity, reflecting the interaction between the brain’s default mode and task positive networks. Such work begins to delineate the neural substrates of the discovered genetic associations with familial ADHD.

Assessing the efficacy of coral restoration along Florida’s coral reef under the chronic persistence of stony coral tissue loss disease - William C. Sharp; Kristene T. Parsons; Erinn M. Muller; Amanda Bourque; David S. Gilliam; Diego Lirman; Colin P. Shea; Joshua D. Voss; John H. Hunt (Frontiers in Marine Science, 2026)
Stony coral tissue loss disease (SCTLD) has caused unprecedented coral mortality across Florida’s Coral Reef (FCR) since 2014, raising concerns about whether coral restoration can succeed under chronic disease conditions and whether outplanting activities may increase disease transmission risk. As the disease transitioned from epizootic outbreak to enzootic persistence, we conducted a large-scale experimental outplanting to assess coral restoration efficacy under chronic SCTLD persistence and to evaluate the relative importance of SCTLD versus non-disease drivers of restoration outcomes. From May 2021 through April 2023, we outplanted 1,165 colonies of three SCTLD-susceptible species ( Montastraea cavernosa, Orbicella faveolata , and Pseudodiploria clivosa ) sourced from land-based facilities and in-water nurseries across six regions spanning FCR and monitored survival and disease incidence. Concurrent surveys of natural coral communities assessed whether outplanting activities affected local SCTLD prevalence. Probabilities of infection per monitoring interval remained <1-2% across all species, regions, and propagation sources throughout the monitoring period. Importantly, outplanting activities did not increase SCTLD prevalence in neighboring natural coral communities. In contrast to the low and relatively uniform disease incidence, variation in coral survival was strongly structured by ecological and operational factors. The overall coral colony survival rate at the end of the study was 77.3% but was influenced by reef stratum (inshore vs. offshore reefs), geographic region, and colony source. M. cavernosa and P. clivosa exhibited higher survival at inshore sites compared to offshore sites, whereas O. faveolata showed no consistent reef stratum effect on survival. Across FCR, survival varied spatially between regions independent of latitude, suggesting local environmental drivers. Colony source effects varied by species. M. cavernosa and P. clivosa from land-based facilities exhibited significantly lower survival than colonies from in-water nurseries, whereas O. faveolata showed no significant differences between propagation sources. Our results indicate that under SCTLD-enzootic conditions, restoration outcomes are shaped more strongly by habitat suitability, geographic context, and propagation-related factors than by SCTLD itself. These findings suggest that coral restoration can proceed within SCTLD-enzootic zones without increasing disease risk to neighboring coral communities or substantially elevating SCTLD-related mortality of outplanted colonies.

Soil Microbial Diversity and Network Organization Respond to Land Use and Agricultural Inputs Worldwide - Zaki Saati‐Santamaría; Sergio Pérez‐Gorjón; Daniel Abel‐Schaad; Alberto Acedo‐Bécares; Francisca Alba‐Sánchez; Amanda Lucia Alves; Weronika Babinska‐Wensierska; Jorge Ariel Marfetán; Carolina Barroetaveña; Kara Barry; Francisco Beitia; Katerina Biniari; et al. (Global Change Biology, 2026)
Soil microbiomes are critical for ecosystem functioning, yet the global influences of climate and agricultural practices on their diversity and structure remain incompletely characterized. Here we analyzed 1921 soil samples from 33 countries worldwide across diverse biomes to assess how climate gradients and agricultural inputs, including pesticides and fertilizers, shape prokaryotic and fungal communities. We found that microbial diversity peaks at intermediate temperatures and differs markedly between natural and agricultural soils, with agriculture increasing microbial diversity while altering community composition and ecological guilds. Pesticide use selectively reduced bacterial diversity and shifted fungal guilds, decreasing ectomycorrhizal fungi while increasing saprotrophs, whereas fertilization reduced microbial network cohesion, with organic and inorganic fertilizers eliciting distinct community responses. These findings reveal that climatic factors and agricultural management jointly influence soil microbial diversity, community structure, and network connectivity, with implications for soil health and ecosystem resilience in managed landscapes. Overall, our results demonstrate that agricultural practices, including the use of pesticides and both organic and inorganic fertilizers, act as strong ecological filters that reshape soil microbiomes worldwide—enhancing apparent diversity but driving a functional shift toward less mutualistic, more fragmented, and potentially less resilient communities.

Coral larvae have unique transcriptomic responses to pathogenic and probiotic bacteria - Erin M. Borbee; Isabella V. Changsut; Kira Bernabe; Alicia Schickle; David Nelson; Koty H. Sharp; Lauren E. Fuess (Coral Reefs, 2026)
The growing prevalence of coral disease and other stressors threatens coral reefs, and evidence suggests these stressors not only affect adult corals but may also have impacts on early life stages. Yet, our understanding of coral larval physiology, including immunological function, is significantly limited. Here, we leverage the temperate coral experimental system Astrangia poculata to investigate the transcript-level response of A. poculata to exposure to pathogenic and probiotic bacteria. The bacteria tested in the experiment were the known coral pathogen ( Vibrio coralliilyticus RE22) and a probiont ( Phaeobacter inhibens S4) previously demonstrated to inhibit the pathogen’s growth. In this study, we aim to (1) characterize the general immune response of A. poculata larvae to bacterial stimuli, (2) identify defense mechanisms that may aid in host resistance to pathogens, and (3) characterize the impacts of probiont exposure on A. poculata larval gene expression. Our data identify both shared and divergent larval immune responses to probiotic and pathogenic bacteria. Immunological peptidases were enriched in response to bacteria—expression of endopeptidases increased in response to probiont and pathogen, and metallopeptidase activity was enriched in response to the pathogen. Clustering analyses further revealed a diverse array of immune components in response to the pathogen, while its response to the probiont was associated with a broad range of developmental and metabolic terms. Collectively, the data from this study identify immune components that may play a role in coral response to bacteria during their early life stages, with broad relevance to current restoration and conservation approaches.

Role of freshwater availability and terrestrial land‐cover change in the distribution of a declining, terrestrial, insectivorous bird - Catrin F. Eden; Simon Gillings; Richard K. Broughton; Bart Donato; Chris M. Hewson; Stuart P. Sharp (Conservation Biology, 2026)
Insectivorous, Afro‐Palearctic migrant birds provide cross‐border ecosystem services, but many are declining rapidly. The complex life cycle of migrant birds makes their conservation difficult, but understanding where they spend time during the breeding season can help indicate where those actions will be most effective. We used the spotted flycatcher ( Muscicapa striata ), a declining, Afro‐Palearctic, migratory insectivore and habitat generalist, as a model to examine how river density and land‐cover change were associated with loss and colonization during the breeding season of 2 × 2‐km national atlas survey areas from 1990 to 2010. Greater river density was associated with a lower probability of loss (odds ratio [OR] 0.8) between survey periods and a higher probability of colonization (OR 1.25). Loss was associated with increases in urban land cover (OR 1.17), and, unexpectedly, colonization was negatively associated with increases in woodland (OR 0.91) and standing freshwater (OR 0.94). Our results suggest that habitat creation is unlikely to provide sufficient benefits for some insectivorous birds within the time needed for population recovery. Thus, efforts should focus on the protection and improvement of established habitats. River density was strongly associated with the persistence of the spotted flycatcher, and this finding highlights that understanding the benefits of freshwater habitat for terrestrial species should be a priority for conservation management.

Climatology and annual cycle of global ocean dissolved oxygen represented by multiple observational gridded products - Juan Du; Lijing Cheng; Takamitsu Ito; Hernan E. Garcia; Zhankun Wang; Jonathan D. Sharp; Christopher J. Roach; Shoshiro Minobe; Yuntao Zhou; Bin Lu; Gian Giacomo Navarra; Seth M. Bushinsky (Ocean Science, 2026)
Ocean dissolved oxygen (O2) is an essential climate variable crucial for sustaining the marine life; thus, changes of O2 at various spatiotemporal scales should be quantified and understood. Here, we study the climatology and annual cycle of O2 at regional to global scales using eight available gridded observational products. These datasets are generated by different groups using different primary data selection, quality control, bias correction, and interpolation methods, including statistical and machine-learning-based mapping methods. A common set of metrics was collaboratively developed by the community of the Gridded Observational Dataset Intercomparison Project-Dissolved Oxygen (GODIP-DO) to facilitate the inter-comparison. We find that global mean O2 profiles are consistent among all products (±3 µmol kg−1), with the well-established decrease from high surface values to a minimum ∼ 1000 m, and subsequent increase to higher O2 at depth, although local differences could reach ±25 µmol kg−1 (0–1000 m). The hemispheric O2 annual cycle correlates strongly with ocean temperature changes, suggesting the key driver of temperature for the O2 annual cycle. However, there is substantial variation in the global mean 0–100 m O2 annual cycle, the magnitude ranges from −1 to 0.8 µmol kg−1, with a standard deviation of the datasets of ∼ 0.3 µmol kg−1. Average oxygen minimum zones (OMZ) volume among the products is 80.92 × 106 km3 (±1.95 %) for a 60 µmol kg−1 threshold and 152.00 × 106 km3 (±1.72 %) for a 90 µmol kg−1 threshold. Our results help to depict and understand the spread among the available O2 gridded datasets.

Dependence of viscosity, thermal diffusivity, and thermal conductivity of East Pacific Rise pillow basalts, glasses, and melts on temperature and hydration - Anne M. Hofmeister; Miriam G. Sharp; Alan G. Whittington (Journal of Volcanology and Geothermal Research, 2026)

Laryngectomy Education and Training Resources: An Environmental Scan of Resources - Laura-Jayne Watson; Emer Fahy; David W. Hamilton; Linda Sharp; Vicky Thornton; Joanne M. Patterson (Journal of Cancer Education, 2026)
In many settings, head and neck cancer (HNC) services are centralized in large hospitals, meaning that community input from HNC specialists can be lacking. Community healthcare professionals often require laryngectomy-specific education and training to provide optimal care to people at home. However, laryngectomy-specific education/training is often sporadic and varies between centres, making it difficult to achieve standardisation in healthcare professionals’ laryngectomy knowledge and skills. This study aimed to identify and critically review existing laryngectomy education/training resources for healthcare professionals, which include elements applicable to community care. We used environmental scanning to systematically and comprehensively identify and examine all available education/training resources which had an element of education and/or training applicable to community laryngectomy care. Eligible resources were reviewed for training-specific details, laryngectomy-specific details, evaluation method, accessibility, and patient and public involvement (PPI). A total of 6655 resources were screened; 49 were eligible for data extraction. There was wide variability in the level of laryngectomy-specific content in the resources. PPI in development was lacking, and data detailing the impact of resources on healthcare professionals’ knowledge/skills and patient outcomes was sparse. This is the first study to systematically identify and appraise laryngectomy education/training resources which have applicability to community care. There is not one consistent approach to education/training development method, content, delivery, or evaluation, likely rendering these ineffective and lacking impact. Community-specific laryngectomy education and training, with clear implementation and evaluation, is required.

Impact of climate change on freshwater macronutrients and agricultural yields across Britain - Nathan Missault; Victoria A. Bell; David M. Cooper; Ryan T. Sharp; Andrew P. Whitmore; Alice E. Milne; Helen N. Davies (Journal of Environmental Management, 2026)

Rethinking land-use Strategies: A multi-objective analysis of combined sparing and sharing approaches applied across great britain - Imane El Fartassi; Ryan T. Sharp; Victoria A. Bell; Andrew P. Whitmore; Helen Metcalfe; Nathan Missault; John Redhead; David M. Cooper; Jonathan Storkey; Helen Davies; Theo Jackson; Kevin Coleman; et al. (Journal of Environmental Management, 2026)

Environmental identities of college students reveal potential conflicts and common ground for wildlife conservation - Richard Von Furstenberg; Lincoln R. Larson; M. Nils Peterson; Kangjae Jerry Lee; Victoria R. Vayer; kathryn stevenson; Stacy A.C. Nelson; Jeremy Bruskotter; Adam A. Ahlers; Christine Anhalt-Depies; Taniya Bethke; Chris Chizinski; et al. (Biological Conservation, 2025)

Cross-system transfer of fatty acids from aquatic insects supports terrestrial insectivore condition and reproductive success - Catrin F. Eden; Richard K. Broughton; Bart Donato; Chris M. Hewson; Caroline Isaksson; Stuart P. Sharp (Oecologia, 2025)
Cross-system fluxes of aquatic insects rich in omega-3 long-chain polyunsaturated fatty acids (ω-3 LC-PUFAs), specifically eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), may subsidise insectivorous vertebrates that are suffering due to terrestrial insect declines. The benefits of high ω-3 LC-PUFA diets, such as improved growth and immunocompetence, have previously been demonstrated for riparian insectivores. Understanding the potential for aquatic insects to benefit a range of species is necessary for informing land management practices. Using the spotted flycatcher ( Muscicapa striata ), a habitat-generalist, insectivorous bird as a model, we tested how blood plasma ω-3 LC-PUFA concentrations and the ratio of ω-6:ω-3 fatty acids were related to the body condition of 14 adults and 84 chicks in the wild. We measured how variation in ω-3 LC-PUFAs and ω-6:ω-3 was related to river proximity, to test whether they were related to aquatic insect availability. We assessed how these relationships may extend beyond the individual level by monitoring flying insect availability throughout two breeding seasons and testing its ability to predict reproductive success. EPA was positively correlated with body condition in chicks and adults and declined with distance from a river. Conversely, ω-6:ω-3 was negatively correlated with body condition and increased with distance from a river. Breeding success was positively correlated with aquatic insect availability, suggesting that access to a high ω-3 LC-PUFA diet has the potential to mitigate declines in generalist insectivores. Our results highlight how the maintenance or creation of high-quality freshwater habitats may be promoted in a conservation context for non-riparian species.

Production of green adhesives from sustainable proteins derived from municipal wastewater treatment plant sludges and potential enhancements from soy protein amending - Chelsea Trahan Zeringue; William M. Chirdon; Wayne Sharp; Daniel Gang; Ahmed Khattab; Rafael Hernandez; William Holmes; Mark E. Zappi (Journal of Environmental Management, 2025)

Corrigendum: Restoration of herbivory on Caribbean coral reefs: are fishes, urchins, or crabs the solution? - Mark J. Butler; Alain Duran; Colette J. Feehan; Alastair R. Harborne; Alwin Hylkema; Joshua T. Patterson; William C. Sharp; Angelo Jason Spadaro; Tom Wijers; Stacey M. Williams (Frontiers in Marine Science, 2025)

Review of APSIM's soil nitrogen modelling capability for agricultural systems analyses - Kirsten Verburg; Heather R. Pasley; Jody S. Biggs; Iris Vogeler; Enli Wang; Henrike Mielenz; Val O. Snow; Chris J. Smith; Chiara Pasut; Andrea D. Basche; Di He; Sotirios V. Archontoulis; et al. (Agricultural Systems, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Micronization of wholewheat flour increases iron bioavailability from hydrothermally processed wheat flour dough - Mohamad F. Aslam; Sarah M. Arafsha; Sarah E. Berry; Balazs Bajka; Peter R. Ellis; Gladys O. Latunde-Dada; Paul A. Sharp (Food Research International, 2024)

A content analysis of parents’ reflections on pathogenic and uncertain pediatric oncology germline sequencing results - Katianne M. Howard Sharp; Mary Egan Clark; Niki Jurbergs; Annastasia Ouma; Lynn Harrison; Leslie Taylor; Kayla Hamilton; Rose B. McGee; Regina Nuccio; Stacy Hines-Dowell; Jami S. Gattuso; Michelle Pritchard; et al. (Familial Cancer, 2024)

Perception of Body Fat and Body Fat Percentages Among Female College Students - M. Schmidt; D. Beeson; S. Keck; T. Pulver; M. Scott; N. Sharp; E. Weaver; C. Lyman; A. Grady (Journal of the Academy of Nutrition and Dietetics, 2024)

COVID-19 Pandemic Telemedicine Compared to Pre-pandemic In-person Delivery of the New Direction® Program for Weight Loss Success - H. Saroka; J. Schwartz; K. Sharp; J. Ponce; C. Hanson; M. Timmerman; M. Jackson (Journal of the Academy of Nutrition and Dietetics, 2024)

Random and systematic uncertainty in ship‐based seawater carbonate chemistry observations - Brendan R. Carter; Jonathan D. Sharp; Maribel I. García‐Ibáñez; Ryan J. Woosley; Michael B. Fong; Marta Álvarez; Leticia Barbero; Simon L. Clegg; Regina Easley; Andrea J. Fassbender; Xinyu Li; Katelyn M. Schockman; et al. (Limnology and Oceanography, 2024)
Seawater carbonate chemistry observations are increasingly necessary to study a broad array of oceanographic challenges such as ocean acidification, carbon inventory tracking, and assessment of marine carbon dioxide removal strategies. The uncertainty in a seawater carbonate chemistry observation comes from unknown random variations and systematic offsets. Here, we estimate the magnitudes of these random and systematic components of uncertainty for the discrete open‐ocean carbonate chemistry measurements in the Global Ocean Data Analysis Project 2022 update (GLODAPv2.2022). We use both an uncertainty propagation approach and a carbonate chemistry measurement “inter‐consistency” approach that quantifies the disagreement between measured carbonate chemistry variables and calculations of the same variables from other carbonate chemistry measurements. Our inter‐consistency analysis reveals that the seawater carbonate chemistry measurement community has collected and released data with a random uncertainty that averages about 1.7 times the uncertainty estimated by propagating the desired “climate‐quality” random uncertainties. However, we obtain differing random uncertainty estimates for subsets of the available data, with some subsets seemingly meeting the climate‐quality criteria. We find that seawater pH measurements on the total scale do not meet the climate‐quality criteria, though the inter‐consistency of these measurements improves (by 38%) when limited to the subset of measurements made using purified indicator dyes. We show that GLODAPv2 adjustments improve inter‐consistency for some subsets of the measurements while worsening it for others. Finally, we provide general guidance for quantifying the random uncertainty that applies for common combinations of measured and calculated values.

Anticoagulant rodenticide exposure in common buzzards: Impact of new rules for rodenticide use - Sheila George; E. Sharp; S. Campbell; A. Giela; C. Senior; L.M. Melton; D. Vyas; L. Mocogni; M. Galloway (Science of The Total Environment, 2024)

Moche chronology of ancient Peru: Bayesian assessment of radiocarbon dates and ceramic styles from north to south - Michele L. Koons; Branden Cesare Rizzuto; Lisa Trever; Alicia Boswell; Augusto Bazán Pérez; Luis A. Muro Ynoñán; Gabriel Prieto; Carlos Rengifo; Kayeleigh Sharp; Edward Swenson; Hugo Ikehara-Tsukayama; Jessica Ortiz Zevallos; et al. (Quaternary International, 2024)

Discovery of imbricated beachrock deposits adjacent to the Java trench, Indonesia: influence of tsunami and storm waves, and implications for mega-thrust earthquakes - R. Harris; W. Meservy; H. Sulaeman; M. Bunds; J. Andreini; B. Sharp; B. Berrett; J. Whitehead; G. Carver; G. Setiadi; S. Hapsoro; C. Prasetyadi (Natural Hazards, 2024)

Bear biometrics: developing an individual recognition technique for sloth bears - Ashish Kumar Jangid; Arun A. Sha; Swayam Thakkar; Nishchay Chawla; Baijuraj M. V.; Thomas Sharp; Kartick Satyanarayan; Geeta Seshamani (Mammalian Biology, 2024)

Restoration of herbivory on Caribbean coral reefs: are fishes, urchins, or crabs the solution? - Mark J. Butler; Alain Duran; Colette J. Feehan; Alastair R. Harborne; Alwin Hylkema; Joshua T. Patterson; William C. Sharp; Angelo Jason Spadaro; Tom Wijers; Stacey M. Williams (Frontiers in Marine Science, 2024)
That coral reefs are in decline worldwide, particularly in the Caribbean, will come as no surprise. This decades-long decline has reached a potential tipping point as the weight of the effects of climate change have come decidedly to bear on the planet’s most diverse marine ecosystem. Whether coral reefs can persist without restorative intervention is debatable, which has prompted a surge in coral reef restoration projects focusing primarily on the cultivation and transplantation of coral fragments onto degraded reefs. But that widespread approach does little to address the underlying causes of coral loss, one of which is the proliferation of macroalgae that are deleterious to corals. An emerging solution to this problem is the enhancement of herbivory on coral reefs through improved management of herbivores, artificial enhancement of herbivore settlement, or their mariculture and subsequent stocking. This review explores the nuances of the biology of well-studied Caribbean coral reef herbivores (fishes, sea urchins, and crabs) as it relates to their mariculture and investigates the promise of herbivore stocking onto coral reefs as a restoration strategy. Fish, urchin, and crab herbivores differ appreciably in life histories, which confers advantages and disadvantages with respect to their mariculture and effectiveness as grazers. Mariculture of herbivorous marine fish for reef restoration is essentially non-existent so the reestablishment of grazing fish abundance on coral reefs focuses primarily on their protection through fishery regulations, but only at a few locations in the Caribbean. Mariculture of herbivorous urchins and crabs for restoration purposes is in its infancy, but promising especially for crabs whose larval rearing is less difficult. Perhaps the biggest challenge for the mariculture of either taxon is “scaling-up” from research settings to large-scale mariculture needed for stocking. Numerous studies extol the benefits of functional redundancy and complementarity for coral reef ecosystem stability, but whether this principal applies to the restoration of grazing function is untested. We identify gaps in our knowledge of best practices for the restoration of grazing function on coral reefs and conclude with some practical guidance on the establishment of targets for macroalgal reduction, along with strategic advice on grazer stocking in a given reef habitat.

Public perceptions of per- and polyfluoroalkyl substances (PFAS): Psycho-demographic characteristics differentiating PFAS knowledge and concern - Joya A. Kemper; Emma Sharp; Shan Yi; Erin M. Leitao; Lokesh P. Padhye; Melanie Kah; Jack L.-Y. Chen; Kapish Gobindlal (Journal of Cleaner Production, 2024)

Microalgae in bioregenerative life support systems for space applications - Emmanuel D. Revellame; Remil Aguda; Kristel M. Gatdula; William Holmes; Dhan Lord Fortela; Wayne Sharp; Daniel Gang; Andrei Chistoserdov; Rafael Hernandez; Mark E. Zappi (Algal Research, 2024)

Uncertainty sources for measurable ocean carbonate chemistry variables - Brendan R. Carter; Jonathan D. Sharp; Andrew G. Dickson; Marta Álvarez; Michael B. Fong; Maribel I. García‐Ibáñez; Ryan J. Woosley; Yuichiro Takeshita; Leticia Barbero; Robert H. Byrne; Wei‐Jun Cai; Melissa Chierici; et al. (Limnology and Oceanography, 2024)
The ocean carbonate system is critical to monitor because it plays a major role in regulating Earth's climate and marine ecosystems. It is monitored using a variety of measurements, and it is commonly understood that all components of seawater carbonate chemistry can be calculated when at least two carbonate system variables are measured. However, several recent studies have highlighted systematic discrepancies between calculated and directly measured carbonate chemistry variables and these discrepancies have large implications for efforts to measure and quantify the changing ocean carbon cycle. Given this, the Ocean Carbonate System Intercomparison Forum (OCSIF) was formed as a working group through the Ocean Carbon and Biogeochemistry program to coordinate and recommend research to quantify and/or reduce uncertainties and disagreements in measurable seawater carbonate system measurements and calculations, identify unknown or overlooked sources of these uncertainties, and provide recommendations for making progress on community efforts despite these uncertainties. With this paper we aim to (1) summarize recent progress toward quantifying and reducing carbonate system uncertainties; (2) advocate for research to further reduce and better quantify carbonate system measurement uncertainties; (3) present a small amount of new data, metadata, and analysis related to uncertainties in carbonate system measurements; and (4) restate and explain the rationales behind several OCSIF recommendations. We focus on open ocean carbonate chemistry, and caution that the considerations we discuss become further complicated in coastal, estuarine, and sedimentary environments.

Transitional dynamics from mercury to cyanide-based processing in artisanal and small-scale gold mining: Social, economic, geochemical, and environmental considerations - Aaron Malone; Linda Figueroa; Weishi Wang; Nicole M. Smith; James F. Ranville; David C. Vuono; Francisco D. Alejo Zapata; Lino Morales Paredes; Jonathan O. Sharp; Christopher Bellona (Science of The Total Environment, 2023)

Continuous home cage monitoring of activity and sleep in mice during repeated paroxetine treatment and discontinuation - Helen M. Collins; Raquel Pinacho; S. K. Eric Tam; Trevor Sharp; David M. Bannerman; Stuart N. Peirson (Psychopharmacology, 2023)
Rationale Non-invasive home cage monitoring is emerging as a valuable tool to assess the effects of experimental interventions on mouse behaviour. A field in which these techniques may prove useful is the study of repeated selective serotonin reuptake inhibitor (SSRI) treatment and discontinuation. SSRI discontinuation syndrome is an under-researched condition that includes the emergence of sleep disturbances following treatment cessation. Objectives We used passive infrared (PIR) monitoring to investigate changes in activity, sleep, and circadian rhythms during repeated treatment with the SSRI paroxetine and its discontinuation in mice. Methods Male mice received paroxetine (10 mg/kg/day, s.c. ) for 12 days, then were swapped to saline injections for a 13 day discontinuation period and compared to mice that received saline injections throughout. Mice were continuously tracked using the Continuous Open Mouse Phenotyping of Activity and Sleep Status (COMPASS) system. Results Repeated paroxetine treatment reduced activity and increased behaviourally-defined sleep in the dark phase. These effects recovered to saline-control levels within 24 h of paroxetine cessation, yet there was also evidence of a lengthening of sleep bouts in the dark phase for up to a week following discontinuation. Conclusions This study provides the first example of how continuous non-invasive home cage monitoring can be used to detect objective behavioural changes in activity and sleep during and after drug treatment in mice. These data suggest that effects of paroxetine administration reversed soon after its discontinuation but identified an emergent change in sleep bout duration, which could be used as a biomarker in future preclinical studies to prevent or minimise SSRI discontinuation symptoms.

Non-industrial private forest owners' preferences for fuel reduction cost-share programs in the southeastern U.S. - Jana Hilsenroth; Kelly A. Grogan; Raelene M. Crandall; Ludie Bond; Misti Sharp (Forest Policy and Economics, 2023)

Correction: Long-chain omega-3 polyunsaturated fatty acids decrease mammary tumor growth, multiorgan metastasis and enhance survival - Saraswoti Khadge; Geoffrey M. Thiele; John Graham Sharp; Timothy R. McGuire; Lynell W. Klassen; Paul N. Black; Concetta C. DiRusso; Leah Cook; James E. Talmadge (Clinical & Experimental Metastasis, 2023)

Conservation genomics of an exploited, popular aquarium trade species: the giant Caribbean sea anemone Condylactis gigantea (Anthozoa: Actiniidae) - Nancy E. Sheridan; Seifu Seyoum; William C. Sharp; Benjamin M. Titus; Marymegan Daly; Christina L. Richards; Aaron W. Schrey (Conservation Genetics, 2023)

Heavy metal removal by the photosynthetic microbial biomat found within shallow unit process open water constructed wetlands - Zhaoxun Yang; Sarah M. Acker; Adam R. Brady; Armando Arenazas Rodríguez; Lino Morales Paredes; Juana Ticona; Giuliana Romero Mariscal; Gary F. Vanzin; James F. Ranville; Jonathan O. Sharp (Science of The Total Environment, 2023)

The blowfly Chrysomya latifrons inhabits fragmented rainforests, but shows no population structure - Nathan J. Butterworth; James F. Wallman; Nikolas P. Johnston; Blake M. Dawson; Joshua Sharp-Heward; Angela McGaughran (Oecologia, 2023)
Climate change and deforestation are causing rainforests to become increasingly fragmented, placing them at heightened risk of biodiversity loss. Invertebrates constitute the greatest proportion of this biodiversity, yet we lack basic knowledge of their population structure and ecology. There is a compelling need to develop our understanding of the population dynamics of a wide range of rainforest invertebrates so that we can begin to understand how rainforest fragments are connected, and how they will cope with future habitat fragmentation and climate change. Blowflies are an ideal candidate for such research because they are widespread, abundant, and can be easily collected within rainforests. We genotyped 188 blowflies ( Chrysomya latifrons ) from 15 isolated rainforests and found high levels of gene flow, a lack of genetic structure between rainforests, and low genetic diversity – suggesting the presence of a single large genetically depauperate population. This highlights that: (1) the blowfly Ch. latifrons inhabits a ~ 1000 km stretch of Australian rainforests, where it plays an important role as a nutrient recycler; (2) strongly dispersing flies can migrate between and connect isolated rainforests, likely carrying pollen, parasites, phoronts, and pathogens along with them; and (3) widely dispersing and abundant insects can nevertheless be genetically depauperate. There is an urgent need to better understand the relationships between habitat fragmentation, genetic diversity, and adaptive potential–especially for poorly dispersing rainforest-restricted insects, as many of these may be particularly fragmented and at highest risk of local extinction.

Surface displacement expression of progressive failure in a sensitive clay landslide observed with long-term UAV monitoring - Michael J. Bentley; Jonathan M. Foster; Joshua J. Potvin; George Bevan; James Sharp; David J. Woeller; W. Andy Take (Landslides, 2023)

Exposure to global change and microplastics elicits an immune response in an endangered coral - Colleen B. Bove; Katharine Greene; Sharla Sugierski; Nicola G. Kriefall; Alexa K. Huzar; Annabel M. Hughes; Koty Sharp; Nicole D. Fogarty; Sarah W. Davies (Frontiers in Marine Science, 2023)
Global change is increasing seawater temperatures and decreasing oceanic pH, driving declines of coral reefs globally. Coral ecosystems are also impacted by local stressors, including microplastics, which are ubiquitous on reefs. While the independent effects of these global and local stressors are well-documented, their interactions remain less explored. Here, we examine the independent and combined effects of global change (ocean warming and acidification) and microplastics exposures on gene expression (GE) and microbial community composition in the endangered coral Acropora cervicornis . Nine genotypes were fragmented and maintained in one of four experimental treatments: 1) ambient conditions (ambient seawater, no microplastics; AMB); 2) microplastics treatment (ambient seawater, microplastics; MP); 3) global change conditions (warm and acidic conditions, no microplastics; OAW); and 4) multistressor treatment (warm and acidic conditions with microplastics; OAW+MP) for 22 days, after which corals were sampled for genome-wide GE profiling and ITS2 and 16S metabarcoding. Overall A. cervicornis GE responses to all treatments were subtle; however, corals in the multistressor treatment exhibited the strongest GE responses, and genes associated with innate immunity were overrepresented in this treatment. ITS2 analyses confirmed that all coral were associated with Symbiodinium ‘fitti’ and 16S analyses revealed similar microbiomes dominated by the bacterial associate Aquarickettsia , suggesting that these A. cervicornis fragments exhibited remarkably low variability in algal and bacterial community compositions. Future work should focus on functional differences across microbiomes, especially Aquarickettsia and viruses, in these responses. Overall, results suggest that when local stressors are coupled with global change, these interacting stressors present unique challenges to this endangered coral species.

Soil pollution driven by duration of urbanisation and dwelling quality in urban areas: An example from Auckland, New Zealand - A.P. Martin; C. Lim; M. Kah; M.S. Rattenbury; K.M. Rogers; E.L. Sharp; R.E. Turnbull (Applied Geochemistry, 2023)

Global patterns in endemicity and vulnerability of soil fungi - Leho Tedersoo; Vladimir Mikryukov; Alexander Zizka; Mohammad Bahram; Niloufar Hagh‐Doust; Sten Anslan; Oleh Prylutskyi; Manuel Delgado‐Baquerizo; Fernando T. Maestre; Jaan Pärn; Maarja Öpik; Mari Moora; et al. (Global Change Biology, 2022)
Fungi are highly diverse organisms, which provide multiple ecosystem services. However, compared with charismatic animals and plants, the distribution patterns and conservation needs of fungi have been little explored. Here, we examined endemicity patterns, global change vulnerability and conservation priority areas for functional groups of soil fungi based on six global surveys using a high‐resolution, long‐read metabarcoding approach. We found that the endemicity of all fungi and most functional groups peaks in tropical habitats, including Amazonia, Yucatan, West‐Central Africa, Sri Lanka, and New Caledonia, with a negligible island effect compared with plants and animals. We also found that fungi are predominantly vulnerable to drought, heat and land‐cover change, particularly in dry tropical regions with high human population density. Fungal conservation areas of highest priority include herbaceous wetlands, tropical forests, and woodlands. We stress that more attention should be focused on the conservation of fungi, especially root symbiotic arbuscular mycorrhizal and ectomycorrhizal fungi in tropical regions as well as unicellular early‐diverging groups and macrofungi in general. Given the low overlap between the endemicity of fungi and macroorganisms, but high conservation needs in both groups, detailed analyses on distribution and conservation requirements are warranted for other microorganisms and soil organisms.

Use of multiple endpoints to assess the impact of captivity on gut flora diversity in Long Island Sound Fundulus heteroclitus - Joseph P. Battaglia; Christian M. Kearney; Kirsten Guerette; Jordan Corbishley; Emily Sanchez; Brennah Kent; Hanna Storie; Emma Sharp; Shane Martin; Matthew Saberito; Jonathan D. Blake; Richard S. Feinn; et al. (Environmental Biology of Fishes, 2022)

The first three records of killer whales ( Orcinus orca ) killing and eating blue whales ( Balaenoptera musculus ) - John A. Totterdell; Rebecca Wellard; Isabella M. Reeves; Brodie Elsdon; Pia Markovic; Machi Yoshida; Ashleigh Fairchild; Gemma Sharp; Robert L. Pitman (Marine Mammal Science, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Current Approaches for Dissolution Similarity Assessment, Requirements, and Global Expectations - Andreas M. Abend; Limin Zhang; Emilija Fredro-Kumbaradzi; Thomas Hoffelder; Michael J. Cohen; Om Anand; Poonam Delvadia; Haritha Mandula; Zhen Zhang; Evangelos Kotzagiorgis; Susan Lum; Victor Gomes Pereira; et al. (The AAPS Journal, 2022)

Dynamics of bacterial blight disease in resistant and susceptible rice varieties - Jennifer T. Niones; Ryan T. Sharp; Dindo King M. Donayre; Eula Gems M. Oreiro; Alice E. Milne; Ricardo Oliva (European Journal of Plant Pathology, 2022)
Bacterial blight ( X. oryzae pv. oryzae ) is a serious disease in rice across the world. To better control the disease, it is important to understand its epidemiology and how key aspects of this (e.g. infection efficiency, and spatial spread) change according to environment (e.g. local site conditions and season), management, and in particular, variety resistance. To explore this, we analysed data on the disease progress on resistant and susceptible varieties of rice grown at four sites in the Philippines across five seasons using a combination of mechanistic modelling and statistical analysis. Disease incidence was generally lower in the resistant variety. However, we found no evidence that the primary infection efficiency was lower in resistant varieties, suggesting that differences were largely due to reduced secondary spread. Despite secondary spread being attributed to splash dispersal which is exacerbated by wind and rain, the wetter sites of Pila and Victoria in south Luzon tended to have lower infection rates than the drier sites in central Luzon. Likewise, we found spread in the dry season can be substantial and should therefore not be ignored. In fact, we found site to be a greater determinant of the number of infection attempts suggesting that other environmental and management factors had greater effect on the disease than climate. Primary infection was characterised by spatially-random observations of disease incidence. As the season progressed, we observed an emerging short-range (1.6 m–4 m) spatial structure suggesting secondary spread was predominantly short-range, particularly where the resistant variety was grown.

Safety and Pharmacokinetics of Intranasally Administered Heparin - Hannah M. Harris; Katherine L. Boyet; Hao Liu; Rohini Dwivedi; Nicole M. Ashpole; Ritesh Tandon; Gene L. Bidwell; Zhi Cheng; Lauren A. Fassero; Christian S. Yu; Vitor H. Pomin; Dipanwita Mitra; et al. (Pharmaceutical Research, 2022)

Correction to: Histamine, mast cell tryptase and post-exercise hypotension in healthy and collapsed marathon runners - I. T. Parsons; M. J. Stacey; L. Faconti; N. Hill; J. O’Hara; E. Walter; B. Farukh; R. McNally; H. Sharp; A. Patten; R. Grimaldi; N. Gall; et al. (European Journal of Applied Physiology, 2021)

Histamine, mast cell tryptase and post-exercise hypotension in healthy and collapsed marathon runners - I. T. Parsons; M. J. Stacey; L. Faconti; N. Hill; J. O’Hara; E. Walter; B. Farukh; R. McNally; H. Sharp; A. Patten; R. Grimaldi; N. Gall; et al. (European Journal of Applied Physiology, 2021)
Purpose Heat stress exacerbates post-exercise hypotension (PEH) and cardiovascular disturbances from elevated body temperature may contribute to exertion-related incapacity. Mast cell degranulation and muscle mass are possible modifiers, though these hypotheses lack practical evidence. This study had three aims: (1) to characterise pre–post-responses in histamine and mast cell tryptase (MCT), (2) to investigate relationships between whole body muscle mass (WBMM) and changes in blood pressure post-marathon, (3) to identify any differences in incapacitated runners. Methods 24 recreational runners were recruited and successfully completed the 2019 Brighton Marathon (COMPLETION). WBMM was measured at baseline. A further eight participants were recruited from incapacitated runners (COLLAPSE). Histamine, MCT, blood pressure, heart rate, body temperature and echocardiographic measures were taken before and after exercise (COMPLETION) and upon incapacitation (COLLAPSE). Results In completion, MCT increased by nearly 50% from baseline ( p = 0.0049), whereas histamine and body temperature did not vary ( p > 0.946). Systolic (SBP), diastolic (DBP) and mean (MAP) arterial blood pressures and systemic vascular resistance (SVR) declined ( p < 0.019). WBMM negatively correlated with $$Δ $$ Δ SBP ( r = − 0.43, p = 0.046). For collapse versus completion, there were significant elevations in MCT (1.77 ± 0.25 μg/L vs 1.18 ± 0.43 μg/L, p = 0.001) and body temperature (39.8 ± 1.3 °C vs 36.2 ± 0.8 °C, p < 0.0001) with a non-significant rise in histamine (9.6 ± 17.9 μg/L vs 13.7 ± 33.9 μg/L, p = 0.107) and significantly lower MAP, DBP and SVR ( p < 0.033). Conclusion These data support the hypothesis that mast cell degranulation is a vasodilatory mechanism underlying PEH and exercise associated collapse. The magnitude of PEH is inversely proportional to the muscle mass and enhanced by concomitant body heating.

Provenance and genetic diversity of the non-native geckos Phelsuma grandis Gray 1870 and Gekko gecko (Linnaeus 1758) in southern Florida, USA - Thomas W. Fieldsend; Kenneth L. Krysko; Paul Sharp; Timothy M. Collins (Biological Invasions, 2021)

Modulation of heroin intake by ovarian hormones in gonadectomized and intact female rats - Mark A. Smith; Sarah B. Ethridge; Tallia Pearson; Huailin Zhang; Madison M. Marcus; Shannon L. Ballard; Alexander T. Casimir; Kenzie M. Potter; Karl T. Schmidt; Jessica L. Sharp; Andrea M. Robinson (Psychopharmacology, 2021)

Toward a global and reproducible science for brain imaging in neurotrauma: the ENIGMA adult moderate/severe traumatic brain injury working group - Alexander Olsen; Talin Babikian; Erin D. Bigler; Karen Caeyenberghs; Virginia Conde; Kristen Dams-O’Connor; Ekaterina Dobryakova; Helen Genova; Jordan Grafman; Asta K. Håberg; Ingrid Heggland; Torgeir Hellstrøm; et al. (Brain Imaging and Behavior, 2021)
The global burden of mortality and morbidity caused by traumatic brain injury (TBI) is significant, and the heterogeneity of TBI patients and the relatively small sample sizes of most current neuroimaging studies is a major challenge for scientific advances and clinical translation. The ENIGMA (Enhancing NeuroImaging Genetics through Meta-Analysis) Adult moderate/severe TBI (AMS-TBI) working group aims to be a driving force for new discoveries in AMS-TBI by providing researchers world-wide with an effective framework and platform for large-scale cross-border collaboration and data sharing. Based on the principles of transparency, rigor, reproducibility and collaboration, we will facilitate the development and dissemination of multiscale and big data analysis pipelines for harmonized analyses in AMS-TBI using structural and functional neuroimaging in combination with non-imaging biomarkers, genetics, as well as clinical and behavioral measures. Ultimately, we will offer investigators an unprecedented opportunity to test important hypotheses about recovery and morbidity in AMS-TBI by taking advantage of our robust methods for large-scale neuroimaging data analysis. In this consensus statement we outline the working group’s short-term, intermediate, and long-term goals.

Development and molecular cytogenetic characterization of Thinopyrum bessarabicum introgression lines in hexaploid and tetraploid wheats - Amit K. Singh; Peng Zhang; Chongmei Dong; Jianbo Li; Smriti Singh; Richard M. Trethowan; Peter J. Sharp (Theoretical and Applied Genetics, 2020)

Vortioxetine reverses medial prefrontal cortex-mediated cognitive deficits in male rats induced by castration as a model of androgen deprivation therapy for prostate cancer - Alexandra M. Sharp; Suphada Lertphinyowong; Samantha S. Yee; Denisse Paredes; Jonathan Gelfond; Teresa L. Johnson-Pais; Robin J. Leach; Michael Liss; April L. Risinger; Anna C. Sullivan; Ian M. Thompson; David A. Morilak (Psychopharmacology, 2019)

Crystalline-rock aquifer system of the Llano Uplift, Central Texas, USA - Neeraja Setlur; John M. Sharp; Brian B. Hunt (Hydrogeology Journal, 2019)

Unoccupied aerial system assessment of entanglement in Northwest Atlantic gray seals ( Halichoerus grypus ) - Maria Clara Iruzun Martins; Lisa Sette; Elizabeth Josephson; Andrea Bogomolni; Kathryn Rose; Sarah M. Sharp; Misty Niemeyer; Michael Moore (Marine Mammal Science, 2019)

An Australian perspective on rewilding - Oisín F. Sweeney; John Turnbull; Menna Jones; Mike Letnic; Thomas M. Newsome; Andy Sharp (Conservation Biology, 2019)
Rewilding is increasingly recognized as a conservation tool but is often context specific, which inhibits broad application. Rewilding in Australia seeks to enhance ecosystem function and promote self‐sustaining ecosystems. An absence of large‐bodied native herbivores means trophic rewilding in mainland Australia has focused on the restoration of functions provided by apex predators and small mammals. Because of the pervasive influence of introduced mesopredators, predator‐proof fences, and establishment of populations on predator‐free islands are common rewilding approaches. This sets Australian rewilding apart from most jurisdictions and provides globally relevant insights but presents challenges to restoring function to broader landscapes. Passive rewilding is of limited utility in arid zones. Although increasing habitat extent and quality in mesic coastal areas may work, it will likely be necessary to undertake active management. Because much of Australia's population is in urban areas, rewilding efforts must include urban areas to maximize effectiveness. Thus rewilding is not synonymous with wilderness and can occur over multiple scales. Rewilding efforts must recognize human effects on other species and benefit both nature and humans. Rewilding in Australia requires development of a shared vision and strategy and proof‐of‐concept projects to demonstrate the benefits. The repackaging of existing conservation activities as rewilding may confuse and undermine the success of rewilding programs and should be avoided. As elsewhere, rewilding in Australia should be viewed as an important conservation tool.

Improved tactile frequency discrimination in musicians - Andréanne Sharp; M. S. Houde; M. Maheu; I. Ibrahim; F. Champoux (Experimental Brain Research, 2019)

Ertapenem for osteoarticular infections in obese patients: a pharmacokinetic study of plasma and bone concentrations - Jonathan Chambers; Madhu Page-Sharp; Sam Salman; John Dyer; Timothy M. E. Davis; Kevin T. Batty; Laurens Manning (European Journal of Clinical Pharmacology, 2019)

Peptide Inhibitor of Complement C1 (PIC1) Inhibits Growth of Pathogenic Bacteria - Pamela S. Hair; Magdielis Gregory Rivera; Adrianne I. Enos; Susan E. Pearsall; Julia A. Sharp; Nazita Yousefieh; Frank A. Lattanzio; Neel K. Krishna; Kenji M. Cunnion (International Journal of Peptide Research and Therapeutics, 2019)

Long-chain omega-3 polyunsaturated fatty acids decrease mammary tumor growth, multiorgan metastasis and enhance survival - Saraswoti Khadge; Geoffrey M. Thiele; John Graham Sharp; Timothy R. McGuire; Lynell W. Klassen; Paul N. Black; Concetta C. DiRusso; Leah Cook; James E. Talmadge (Clinical & Experimental Metastasis, 2018)

Foundation species patch configuration mediates salt marsh biodiversity, stability and multifunctionality - Sinéad M. Crotty; Sean J. Sharp; Ada C. Bersoza; Kimberly D. Prince; Katheryne Cronk; Emma E. Johnson; Christine Angelini (Ecology Letters, 2018)
Foundation species enhance biodiversity and multifunctionality across many systems; however, whether foundation species patch configuration mediates their ecological effects is unknown. In a 6‐month field experiment, we test which attributes of foundation species patch configuration – i.e. patch size, total patch area, perimeter, area‐perimeter ratio, or connectivity – control biodiversity, stability and multifunctionality by adding a standardised density of mussel foundation species in patches of 1, 5, 10, 30, 60, 90 or 180 individuals to a southeastern US salt marsh. Over 67% of response variables increased with clustering of mussels, responses that were driven by increases in area–perimeter ratio (33%), decreases in perimeter (29%), or increases in patch size (5%), suggesting sensitivity to external stressors and/or dependence on foundation species‐derived niche availability and segregation. Thus, mussel configuration – by controlling the relative distribution of multidimensional patch interior and edge niche space – critically modulates this foundation species’ effects on ecosystem structure, stability and function.

Update to the Global Climate Data package: analysis of empirical bias correction methods in the context of producing very high resolution climate projections - Thomas M. Mosier; David F. Hill; Kendra V. Sharp (International Journal of Climatology, 2018)
While global climate models (GCMs) are useful for simulating climatic responses to perturbations in the Earth's climate system, there are many instances where higher spatial resolution information is necessary. In all instances, interpretation of interpolated or downscaled GCMs must be done cautiously because each method has its own set of assumptions and potential disadvantages. Here, we present an update to the Global Climate Data (GCD) package, which enables the package to efficiently bias correct and interpolate precipitation and air temperature output from GCM simulations to very high spatial resolutions using the delta change method. While the delta change method is relatively simple, it has previously been shown to enhance the physical representation of interpolated climate time‐series compared to directly interpolating the gridded climate time‐series to a higher spatial resolution. The bias correction methods programmed into the GCD package are univariate empirical quantile mapping (QM) and bivariate empirical joint bias correction (JBC). The skill of QM and JBC for improving GCM simulations processed with the delta change method is evaluated through comparing the cumulative distribution functions (CDFs) of the interpolated GCM simulations to the CDFs of Global Historical Climatology Network (GHCN) station observations for three test regions: Oregon (in the USA), the Alps (spanning several countries in Europe), and the Ganges Delta (in India and Bangladesh). We also assess the representation of precipitation and mean temperature joint probability distributions relative to those present in GHCN station observations. Overall, GCM simulations that are bias corrected with QM prior to being input to the delta change method perform best under our analysis.

Characterization and Separation of Cancer Cells with a Wicking Fiber Device - Suzanne M. Tabbaa; Julia L. Sharp; Karen J. L. Burg (Annals of Biomedical Engineering, 2017)

Biomarkers of Acute Stroke Etiology (BASE) Study Methodology - Edward C. Jauch; Andrew D. Barreto; Joseph P. Broderick; Doug M. Char; Brett L. Cucchiara; Thomas G. Devlin; Alison J. Haddock; William J. Hicks; Brian C. Hiestand; Glen C. Jickling; Jeff June; David S. Liebeskind; et al. (Translational Stroke Research, 2017)

Growth, survival, and competitive ability of chestnut (Castanea Mill.) seedlings planted across a gradient of light levels - Cornelia C. Pinchot; Scott E. Schlarbaum; Stacy L. Clark; Arnold M. Saxton; Ami M. Sharp; Callie J. Schweitzer; Frederick V. Hebard (New Forests, 2017)

Functional neuroimaging of visuo-vestibular interaction - R. E. Roberts; H. Ahmad; Q. Arshad; M. Patel; D. Dima; R. Leech; B. M. Seemungal; D. J. Sharp; A. M. Bronstein (Brain Structure and Function, 2017)

Comparison of Blood Viscoelasticity in Pediatric and Adult Cardiac Patients - M. Keith Sharp; Mary Gregg; Guy Brock; Neema Nair; Sarina Sahetya; Erle H. Austin; Christopher Mascio; Mark D. Slaughter; George M. Pantalos (Cardiovascular Engineering and Technology, 2017)

Molecular variability and phylogenetic relationships of guava (Psidium guajava L.) cultivars using inter-primer binding site (iPBS) and microsatellite (SSR) markers - A. Mehmood; S. Luo; N. M. Ahmad; C. Dong; T. Mahmood; Y. Sajjad; M. J. Jaskani; P. Sharp (Genetic Resources and Crop Evolution, 2016)

Erratum to: Impact of Bi-Axial Shear on Atherogenic Gene Expression by Endothelial Cells - Amlan Chakraborty; Sutirtha Chakraborty; Venkatakrishna R. Jala; Jonathan M. Thomas; M. Keith Sharp; R. Eric Berson; Bodduluri Haribabu (Annals of Biomedical Engineering, 2016)

Impact of Bi-Axial Shear on Atherogenic Gene Expression by Endothelial Cells - Amlan Chakraborty; Sutirtha Chakraborty; Venkatakrishna R. Jala; Jonathan M. Thomas; M. Keith Sharp; R. Eric Berson; Bodduluri Haribabu (Annals of Biomedical Engineering, 2016)

Effects of the potential lithium-mimetic, ebselen, on impulsivity and emotional processing - Charles Masaki; Ann L. Sharpley; Charlotte M. Cooper; Beata R. Godlewska; Nisha Singh; Sridhar R. Vasudevan; Catherine J. Harmer; Grant C. Churchill; Trevor Sharp; Robert D. Rogers; Philip J. Cowen (Psychopharmacology, 2016)

Understanding Climate Adaptation on Public Lands in the Upper Midwest: Implications for Monitoring and Tracking Progress - Christine M. Anhalt-Depies; Tricia Gorby Knoot; Adena R. Rissman; Anthony K. Sharp; Karl J. Martin (Environmental Management, 2016)

Peristalsis with Oscillating Flow Resistance: A Mechanism for Periarterial Clearance of Amyloid Beta from the Brain - M. Keith Sharp; Alexandra K. Diem; Roy O. Weller; Roxana O. Carare (Annals of Biomedical Engineering, 2016)

A comparison of postrelease survival parameters between single and mass stranded delphinids from Cape Cod, Massachusetts, U.S.A. - Sarah M. Sharp; Charles T. Harry; Jane M. Hoppe; Kathleen M. Moore; Misty E. Niemeyer; Ian Robinson; Kathryn S. Rose; W. Brian Sharp; Scott Landry; Jessica Richardson; Michael J. Moore (Marine Mammal Science, 2016)
The viability of healthy single stranded dolphins as immediate release candidates has received little attention. Responders have been reluctant to release lone delphinids due to their social needs, even when they pass the same health evaluations as mass stranded animals. This study tracked postrelease success of 34 relocated and released satellite tagged delphinids from single and mass strandings. Three postrelease survival parameters (transmission duration, swim speed, and daily distance) were examined to evaluate whether they differed among single stranded/single released ( SS / SR ), mass stranded/single released ( MS / SR ), or mass stranded/mass released ( MS / MR ) dolphin groups. Comparisons were also made between healthy and borderline release candidates. Satellite tags transmitted for a mean of 21.2 d ( SD = 19.2, range = 1–79), daily distance traveled was 42.0 km/d (11.25, 20.96–70.72), and swim speed was 4.3 km/h (1.1, 2.15–8.54). Postrelease parameters did not differ between health status groups, however, SS / SR dolphins transmitted for a shorter mean duration than MS / MR and MS / SR groups. Postrelease vessel‐based surveys confirmed conspecific group location for two healthy, MS / SR dolphins. Overall, these results support the potential to release healthy stranded single delphinids; however, further refinement of health assessment protocols for these challenging cases is needed.

Fairway patch - a serious emerging disease of couch (syn. bermudagrass) [Cynodon dactylon] and kikuyu (Pennisetum clandestinum) turf in Australia caused by Phialocephala bamuru P.T.W. Wong & C. Dong sp. nov. - P. T. W. Wong; C. Dong; P. M. Martin; P. J. Sharp (Australasian Plant Pathology, 2015)

Basolateral amygdala and ventral hippocampus in stress-induced amplification of nicotine self-administration during reacquisition in rat - Guoliang Yu; Burt M. Sharp (Psychopharmacology, 2015)

Variability in summer anticyclonic circulation over the Canadian Arctic Archipelago and west Greenland in the late 20th/early 21st centuries and its effect on glacier mass balance - P. Bezeau; M. Sharp; G. Gascon (International Journal of Climatology, 2015)
More frequent summer anticyclonic circulation over the Canadian Arctic Archipelago ( CAA ) between 2007 and 2012 caused more intense and sustained melt of ice caps and glaciers and increased rates of mass loss. To determine the frequency of the occurrence of anticyclonic circulation over the CAA and western Greenland, a self‐organizing map ( SOM ) was used to classify daily 500 hPa geopotential height (GPH) anomalies calculated from National Centers for Environmental Prediction and the National Center for Atmospheric Research ( NCEP / NCAR ) Reanalysis 1 (1948–2012) and five Coupled Model Intercomparison Project Phase 5 ( CMIP5 ) models (1950–2025). While the NCEP / NCAR reanalysis indicates that significant summer warming over the CAA is linked to a doubling in the frequency of anticyclonic circulation over the region since 2007, the CMIP5 models were not capable of reproducing the magnitude of the trend in the frequency of anticyclonic circulation over the CAA and western Greenland found in NCEP / NCAR . The variability of the frequency of positive anomalies in summer 500 hPa GPH was found to be related to variability of Arctic sea ice volume/thickness in April, May and June (1979–2012) and to poleward eddy heat flux in June (1979–2012).

Amplified reacquisition of nicotine self-administration in rats by repeated stress during abstinence - Guoliang Yu; Hao Chen; Burt M. Sharp (Psychopharmacology, 2014)

Clinical and genomic evaluation of 201 patients with Phelan–McDermid syndrome - Sara M. Sarasua; Luigi Boccuto; Julia L. Sharp; Alka Dwivedi; Chin-Fu Chen; Jonathan D. Rollins; R. Curtis Rogers; Katy Phelan; Barbara R. DuPont (Human Genetics, 2014)

Hematological, biochemical, and morphological parameters as prognostic indicators for stranded common dolphins ( Delphinus delphis) from Cape Cod, Massachusetts, U.S.A. - Sarah M. Sharp; Joyce S. Knoll; Michael J. Moore; Kathleen M. Moore; Charles T. Harry; Jane M. Hoppe; Misty E. Niemeyer; Ian Robinson; Kathryn S. Rose; W. Brian Sharp; David Rotstein (Marine Mammal Science, 2014)
The current paucity of published blood values and other clinically relevant data for short‐beaked common dolphins, Delphinus delphis, hinders the ability of veterinarians and responders to make well‐informed diagnoses and disposition decisions regarding live strandings of this species. This study examined hematologic, clinical chemistry, and physical parameters from 26 stranded common dolphins on Cape Cod, Massachusetts, in light of their postrelease survival data to evaluate each parameter's efficacy as a prognostic indicator. Statistically and clinically significant differences were found between failed and survived dolphins, including lower hematocrit, hemoglobin, TCO 2 , and bicarbonate and higher blood urea nitrogen, uric acid, and length‐to‐girth ratios in animals that failed. In general when compared to survivors, failed dolphins exhibited acidosis, dehydration, lower PCV s, and decreased body condition. Additionally, failed dolphins had the highest ALT , AST , CK , LDH , GGT , and lactate values. These blood values combined with necropsy findings indicate that there are likely a variety of factors affecting postrelease survival, including both preexisting illness and stranding‐induced conditions such as capture myopathy. Closer evaluation of these parameters for stranded common dolphins on point of care analyzers in the field may allow stranding personnel to make better disposition decisions in the future.

30‐Arcsecond monthly climate surfaces with global land coverage - Thomas M. Mosier; David F. Hill; Kendra V. Sharp (International Journal of Climatology, 2014)
Monthly total precipitation and mean temperature climate surfaces, gridded to 30‐arcseconds (≈1 km at the equator) and available for all global land areas, are presented. These datasets are generated with a Delta downscaling method, using the 30‐arcsecond WorldClim climatologies to scale monthly anomaly grids. For monthly mean temperature, the anomalies are constructed from both the Climate Research Unit ( CRU ) and Willmott & Matsuura (W&M) 0.5 degree time‐series datasets, whereas for monthly precipitation Global Precipitation Climatology Centre ( GPCC ) data are also used. The 0.5 degree anomalies are then interpolated to the 30‐arcsecond resolution. Use of piecewise cubic Hermite interpolating polynomials (PCHIP) to interpolate the anomaly grids results in more physically representative Delta downscaled surfaces, compared to bilinear and cubic spline interpolation. The Delta downscaled products are compared to Global Historical Climatology Network ( GHCN ) station records for six test regions distributed globally. In this analysis, the Delta grids produced using the W&M time‐series dataset perform better than grids produced using GPCC or CRU . Using Oregon, USA as a test region, the Delta downscaled datasets are compared to the Parameter‐elevation Regressions on Independent Slopes Model ( PRISM ) datasets. For monthly precipitation, PRISM performs better than each of the three Delta downscaled datasets, but for mean temperature both Delta downscaled datasets outperform PRISM . Through computing the Pearson product–moment correlation coefficient between GHCN station delineated errors in the WorldClim climatologies and the Delta downscaled W&M data, it is shown that performance of the Delta grids corresponds strongly to performance of the reference climatologies. Therefore, future improvement of the 30‐arcsecond Delta grids described in this article is strongly tied to advances in the high‐resolution climatological data for all global land surfaces. The Delta downscaled datasets discussed herein are open‐source and freely distributed at http://www.globalclimatedata.org .

Distribution and diversity of V errucomicrobia methanotrophs in geothermal and acidic environments - Christine E. Sharp; Angela V. Smirnova; Jaime M. Graham; Matthew B. Stott; Roshan Khadka; Tim R. Moore; Stephen E. Grasby; Maria Strack; Peter F. Dunfield (Environmental Microbiology, 2014)
Summary Recently, methanotrophic members of the phylum V errucomicrobia have been described, but little is known about their distribution in nature. We surveyed methanotrophic bacteria in geothermal springs and acidic wetlands via pyrosequencing of 16 S rRNA gene amplicons. Putative methanotrophic V errucomicrobia were found in samples covering a broad temperature range (22.5–81.6° C ), but only in acidic conditions ( pH 1.8–5.0) and only in geothermal environments, not in acidic bogs or fens. Phylogenetically, three 16 S rRNA gene sequence clusters of putative methanotrophic V errucomicrobia were observed. Those detected in high‐temperature geothermal samples (44.1–81.6° C ) grouped with known thermoacidiphilic ‘ M ethylacidiphilum ’ isolates. A second group dominated in moderate‐temperature geothermal samples (22.5–40.1° C ) and a representative mesophilic methanotroph from this group was isolated (strain LP 2 A ). Genome sequencing verified that strain LP 2 A possessed particulate methane monooxygenase, but its 16 S rRNA gene sequence identity to ‘ M ethylacidiphilum infernorum ’ strain V4 was only 90.6%. A third group clustered distantly with known methanotrophic V errucomicrobia . Using pmoA ‐gene targeted quantitative polymerase chain reaction, two geothermal soil profiles showed a dominance of LP 2 A ‐like pmoA sequences in the cooler surface layers and ‘ M ethylacidiphilum'‐ like pmoA sequences in deeper, hotter layers. Based on these results, there appears to be a thermophilic group and a mesophilic group of methanotrophic V errucomicrobia . However, both were detected only in acidic geothermal environments.

Estimates of recharge in two arid basin aquifers: a model of spatially variable net infiltration and its implications (Red Light Draw and Eagle Flats, Texas, USA) - Wendy Marie Robertson; John M. Sharp (Hydrogeology Journal, 2013)

Soil–plant N processes in a High Arctic ecosystem, NW Greenland are altered by long‐term experimental warming and higher rainfall - Sean M. Schaeffer; Elizabeth Sharp; Joshua P. Schimel; Jeffery M. Welker (Global Change Biology, 2013)
Rapid temperature and precipitation changes in High Arctic tundra ecosystems are altering the biogeochemical cycles of carbon (C) and nitrogen (N), but in ways that are difficult to predict. The challenge grows from the uncertainty of N cycle responses and the extent to which shifts in soil N are coupled with the C cycle and productivity of tundra systems. We used a long‐term (since 2003) experiment of summer warming and supplemental summer water additions to a High Arctic ecosystem in NW Greenland, and applied a combination of discrete sampling and in situ soil core incubations to measure C and N pools and seasonal microbial processes that might control plant‐available N. We hypothesized that elevated temperature and increased precipitation would stimulate microbial activity and net inorganic N mineralization, thereby increasing plant N‐availability through the growing season. While we did find increased N mineralization rates under both global change scenarios, water addition also significantly increased net nitrification rates, loss of NO 3 − ‐N via leaching, and lowered rates of labile organic N production. We also expected the chronic warming and watering would lead to long‐term changes in soil N‐cycling that would be reflected in soil δ 15 N values. We found that soil δ 15 N decreased under the different climate change scenarios. Our results suggest that temperature accelerates biological processes and existing C and N transformations, but moisture increases soil hydraulic connectivity and so alters the pathways, and changes the fate of the products of C and N transformations. In addition, our findings indicate that warmer, wetter High Arctic tundra will be cycling N and C in ways that may transform these landscapes in part leading to greater C sequestration, but simultaneously, N losses from the upper soil profile that may be transported to depth dissolved in water and or transported off site in lateral flow.

Assessing the sensitivity of habitats to fishing: from seabed maps to sensitivity maps a - N. C. Eno; C. L. J. Frid; K. Hall; K. Ramsay; R. A. M. Sharp; D. P. Brazier; S. Hearn; K. M. Dernie; K. A. Robinson; O. A. L. Paramor; L. A. Robinson (Journal of Fish Biology, 2013)
In the Welsh part of the Irish Sea, a method was developed for assessing the sensitivity of different seabed habitats to existing fishing activities, across a range of potential fishing intensities. The resistance of 31 habitats and their associated biological assemblage to damage by 14 categories of fishing activity were assessed along with the rate at which each habitat would recover following impact (resilience). Sensitivity was scored based on a combination of the resistance of a habitat to damage and its subsequent rate of recovery. The assessments were based, wherever possible, on scientific literature, with expert judgement used to extrapolate results to habitat and gear combinations not directly examined in the published literature. The resulting sensitivity matrices were then subject to further peer review at a series of workshops. Following consensus on the habitat sensitivity, these data were combined with the most resolved sea‐floor habitat maps. These habitat sensitivity maps can help inform the development of site‐specific management plans, as well as having a place in spatial planning and aiding managers in developing dialogue with other stakeholders. A case study of their application is provided.

Fostering itself increases nicotine self-administration in young adult male rats - Emily E. Roguski; Hao Chen; Burt M. Sharp; Shannon G. Matta (Psychopharmacology, 2013)

Space physiology IV: mathematical modeling of the cardiovascular system in space exploration - M. Keith Sharp; Jerry Joseph Batzel; Jean-Pierre Montani (European Journal of Applied Physiology, 2013)

Monitoring agricultural rodenticide use and secondary exposure of raptors in Scotland - J. Hughes; E. Sharp; M. J. Taylor; L. Melton; G. Hartley (Ecotoxicology, 2013)

CDER Risk Assessment Exercise to Evaluate Potential Risks from the Use of Nanomaterials in Drug Products - Celia N. Cruz; Katherine M. Tyner; Lydia Velazquez; Kenneth C. Hyams; Abigail Jacobs; Arthur B. Shaw; Wenlei Jiang; Robert Lionberger; Peter Hinderling; Yoon Kong; Paul C. Brown; Tapash Ghosh; et al. (The AAPS Journal, 2013)

Maximizing information from space data resources: a case for expanding integration across research disciplines - Nandu Goswami; Jerry J. Batzel; Gilles Clément; T. Peter Stein; Alan R. Hargens; M. Keith Sharp; Andrew P. Blaber; Peter G. Roma; Helmut G. Hinghofer-Szalkay (European Journal of Applied Physiology, 2013)

Apical-Ventricular Cannula for Aortic Valve Bypass Therapy - Kevin G. Soucy; Joel D. Graham; Carrie J. Benzinger; M. Keith Sharp; Guruprasad A. Giridharan; Michael A. Sobieski; Mark S. Slaughter; Steven C. Koenig (Cardiovascular Engineering and Technology, 2013)

Regulation of glucocorticoid metabolism in the boar testis and caput epididymidis by the gonadotrophin-cAMP signalling pathway - Victoria Cabrera-Sharp; Samantha M. Mirczuk; Elaine Shervill; Anthony E. Michael; Robert C. Fowkes (Cell and Tissue Research, 2013)

Complex carbon cycle responses to multi‐level warming and supplemental summer rain in the high A rctic - Elizabeth D. Sharp; Patrick F. Sullivan; Heidi Steltzer; Adam Z. Csank; Jeffrey M. Welker (Global Change Biology, 2013)
The Arctic has experienced rapid warming and, although there are uncertainties, increases in precipitation are projected to accompany future warming. Climate changes are expected to affect magnitudes of gross ecosystem photosynthesis ( GEP ), ecosystem respiration ( ER ) and the net ecosystem exchange of CO 2 ( NEE ). Furthermore, ecosystem responses to climate change are likely to be characterized by nonlinearities, thresholds and interactions among system components and the driving variables. These complex interactions increase the difficulty of predicting responses to climate change and necessitate the use of manipulative experiments. In 2003, we established a long‐term, multi‐level and multi‐factor climate change experiment in a polar semidesert in northwest G reenland. Two levels of heating (30 and 60 W m −2 ) were applied and the higher level was combined with supplemental summer rain. We made plot‐level measurements of CO 2 exchange, plant community composition, foliar nitrogen concentrations, leaf δ 13 C and NDVI to examine responses to our treatments at ecosystem‐ and leaf‐levels. We confronted simple models of GEP and ER with our data to test hypotheses regarding key drivers of CO 2 exchange and to estimate growing season CO 2 ‐C budgets. Low‐level warming increased the magnitude of the ecosystem C sink. Meanwhile, high‐level warming made the ecosystem a source of C to the atmosphere. When high‐level warming was combined with increased summer rain, the ecosystem became a C sink of magnitude similar to that observed under low‐level warming. Competition among our ER models revealed the importance of soil moisture as a driving variable, likely through its effects on microbial activity and nutrient cycling. Measurements of community composition and proxies for leaf‐level physiology suggest GEP responses largely reflect changes in leaf area of S alix arctica , rather than changes in leaf‐level physiology. Our findings indicate that the sign and magnitude of the future High A rctic C budget may depend upon changes in summer rain.

Aquifer-yield continuum as a guide and typology for science-based groundwater management - Suzanne A. Pierce; John M. Sharp; Joseph H. A. Guillaume; Robert E. Mace; David J. Eaton (Hydrogeology Journal, 2013)

Variability and change in the Canadian cryosphere - C. Derksen; S. L. Smith; M. Sharp; L. Brown; S. Howell; L. Copland; D. R. Mueller; Y. Gauthier; C. G. Fletcher; A. Tivy; M. Bernier; J. Bourgeois; et al. (Climatic Change, 2012)
During the International Polar Year (IPY), comprehensive observational research programs were undertaken to increase our understanding of the Canadian polar cryosphere response to a changing climate. Cryospheric components considered were snow, permafrost, sea ice, freshwater ice, glaciers and ice shelves. Enhancement of conventional observing systems and retrieval algorithms for satellite measurements facilitated development of a snapshot of current cryospheric conditions, providing a baseline against which future change can be assessed. Key findings include: 1. surface air temperatures across the Canadian Arctic exhibit a warming trend in all seasons over the past 40 years. A consistent pan-cryospheric response to these warming temperatures is evident through the analysis of multi-decadal datasets; 2. in recent years (including the IPY period) a higher rate of change was observed compared to previous decades including warming permafrost, reduction in snow cover extent and duration, reduction in summer sea ice extent, increased mass loss from glaciers, and thinning and break-up of the remaining Canadian ice shelves. These changes illustrate both a reduction in the spatial extent and mass of the cryosphere and an increase in the temporal persistence of melt related parameters. The observed changes in the cryosphere have important implications for human activity including the close ties of northerners to the land, access to northern regions for natural resource development, and the integrity of northern infrastructure.

Methanogenic potential of Arctic and Antarctic subglacial environments with contrasting organic carbon sources - Marek Stibal; Jemma L. Wadham; Grzegorz P. Lis; Jon Telling; Richard D. Pancost; Ashley Dubnick; Martin J. Sharp; Emily C. Lawson; Catriona E. H. Butler; Fariha Hasan; Martyn Tranter; Alexandre M. Anesio (Global Change Biology, 2012)
Subglacial environments are largely anoxic, contain organic carbon ( OC ) overridden by glacier ice during periods of advance, and harbour active microbial communities. This creates favourable conditions for OC degradation via methanogenesis. It has been hypothesized that OC beneath ice sheets is converted to methane ( CH 4 ) and may be released to the atmosphere during retreat. However, there are limited data available to support this contention. Here, we present new data on the abundance, diversity and activity of methanogenic archaea and the amount and character of OC in subglacial sediments from Arctic and Antarctic glacial systems based on different substrate types. We employed long‐term laboratory incubations to quantify the CH 4 production potential in different subglacial settings. Significant numbers of methanogens (up to 7 × 10 4 cells g −1 ) were detected in the samples and clones of Methanomicrobiales and Methanosarcinales were identified in clone libraries. Long lag periods (up to >200 days) were observed before significant CH 4 concentrations were measured. We report order of magnitude differences in rates of CH 4 production (10 1 –10 5 fmol g −1 d −1 ) in different subglacial sediments, reflecting contrasts in the origin of the sediment and the OC character. Hence, we predict that contrasting rates of CH 4 production are likely to occur beneath glaciers and ice sheets that overran different types of substrate. We subsequently estimated the potential for CH 4 production beneath the Laurentide/Inuitian/Cordilleran and Fennoscandian Ice Sheets during a typical 85 ka Quaternary glacial/interglacial cycle. CH 4 production from lacustrine‐derived OC is likely to be an order of magnitude higher (~6.3–27 Pg C) than that from overridden soils (~0.55–0.68 Pg C), possibly due to a difference in lability between lacustrine and soil OC . While representing a fraction of the entire OC pool (~418–610 Pg C), this finding highlights the importance of considering the character of different OC pools when calculating subglacial CH 4 production.

Functional convergence of microbes associated with temperate marine sponges - M. Ribes; E. Jiménez; G. Yahel; P. López‐Sendino; B. Diez; R. Massana; J. H. Sharp; R. Coma (Environmental Microbiology, 2012)
Summary Most marine sponges establish a persistent association with a wide array of phylogenetically and physiologically diverse microbes. To date, the role of these symbiotic microbial communities in the metabolism and nutrient cycles of the sponge‐microbe consortium remains largely unknown. We identified and quantified the microbial communities associated with three common Mediterranean sponge species, Dysidea avara , Agelas oroides and Chondrosia reniformis ( Demospongiae ) that cohabitate coralligenous community. For each sponge we quantified the uptake and release of dissolved organic carbon (DOC) and nitrogen (DON), inorganic nitrogen and phosphate. Low microbial abundance and no evidence for DOC uptake or nitrification were found for D. avara . In contrast A. oroides and C. reniformis showed high microbial abundance (30% and 70% of their tissue occupied by microbes respectively) and both species exhibited high nitrification and high DOC and NH 4 + uptake. Surprisingly, these unique metabolic pathways were mediated in each sponge species by a different, and host specific, microbial community. The functional convergence of microbial consortia found in these two sympatric sponge species, suggest that these metabolic processes may be of special relevance to the success of the holobiont.

Prokaryotic diversity in sediments beneath two polar glaciers with contrasting organic carbon substrates - Marek Stibal; Fariha Hasan; Jemma L. Wadham; Martin J. Sharp; Alexandre M. Anesio (Extremophiles, 2012)

Deep Autotrophic Soil Respiration in Shrubland and Woodland Ecosystems in Central New Mexico - D. O. Breecker; L. D. McFadden; Z. D. Sharp; M. Martinez; M. E. Litvak (Ecosystems, 2012)

Gene Expression Profiling of Blood in Brain Arteriovenous Malformation Patients - Shantel M. Weinsheimer; Huichun Xu; Achal S. Achrol; Boryana Stamova; Charles E. McCulloch; Ludmila Pawlikowska; Yingfang Tian; Nerissa U. Ko; Michael T. Lawton; Gary K. Steinberg; Steven D. Chang; Glen Jickling; et al. (Translational Stroke Research, 2011)

The Changing Arctic Cryosphere and Likely Consequences: An Overview - M. S. Olsen; T. V. Callaghan; J. D. Reist; L. O. Reiersen; D. Dahl-Jensen; M. A. Granskog; B. Goodison; G. K. Hovelsrud; M. Johansson; R. Kallenborn; J. Key; A. Klepikov; et al. (Ambio, 2011)

Ecological Implications of Changes in the Arctic Cryosphere - Warwick F. Vincent; Terry V. Callaghan; Dorthe Dahl-Jensen; Margareta Johansson; Kit M. Kovacs; Christine Michel; Terry Prowse; James D. Reist; Martin Sharp (Ambio, 2011)

Impact of PSA testing and prostatic biopsy on cancer incidence and mortality: comparative study between the Republic of Ireland and Northern Ireland - A-E. Carsin; F. J. Drummond; A. Black; P. J. van Leeuwen; L. Sharp; L. J. Murray; D. Connolly; L. Egevad; M. Boniol; P. Autier; H. Comber; A. Gavin (Cancer Causes & Control, 2010)

Combined resistance and endurance training improves physical capacity and performance on tactical occupational tasks - Nathan R. Hendrickson; Marilyn A. Sharp; Joseph A. Alemany; Leila A. Walker; Everett A. Harman; Barry A. Spiering; Disa L. Hatfield; Linda M. Yamamoto; Carl M. Maresh; William J. Kraemer; Bradley C. Nindl (European Journal of Applied Physiology, 2010)

Simulated Stand Tests and Centrifuge Training to Prevent Orthostatic Intolerance on Earth, Moon, and Mars - Brandon W. Coats; M. Keith Sharp (Annals of Biomedical Engineering, 2010)

Activation of 5-HT6 receptors facilitates attentional set shifting - Katherine E. Burnham; Mark G. Baxter; John R. Bainton; Eric Southam; Lee A. Dawson; David M. Bannerman; Trevor Sharp (Psychopharmacology, 2010)

Television viewing time and weight gain in colorectal cancer survivors: a prospective population-based study - Katrien Wijndaele; Brigid M. Lynch; Neville Owen; David W. Dunstan; Stephen Sharp; Joanne F. Aitken (Cancer Causes & Control, 2009)

Identification of novel ω -gliadin gene in Aegilops tauschii using RFLP - M. Hassani; M. Naghavi; M. Shariflou; P. Sharp (Cereal Research Communications, 2009)

Mice overexpressing the 5-hydroxytryptamine transporter show no alterations in feeding behaviour and increased non-feeding responses to fenfluramine - A. Pringle; K. A. Jennings; S. Line; D. M. Bannerman; S. Higgs; T. Sharp (Psychopharmacology, 2008)

The potential for seaweed resource development in subarctic Canada; Nunavik, Ungava Bay - G. Sharp; M. Allard; A. Lewis; R. Semple; G. Rochefort (Journal of Applied Phycology, 2008)

Evaluation of Mechanisms of Postflight Orthostatic Intolerance with a Simple Cardiovascular System Model - Justin Broskey; M. Keith Sharp (Annals of Biomedical Engineering, 2007)

Simultaneous blockade of 5-HT1A/B receptors and 5-HT transporters results in acute increases in extracellular 5-HT in both rats and guinea pigs: in vivo characterization of the novel 5-HT1A/B receptor antagonist/5-HT transport inhibitor SB-649915-B - Zoë A. Hughes; Kathryn R. Starr; Claire M. Scott; Michael J. Newson; Trevor Sharp; Jeannette M. Watson; Jim J. Hagan; Lee A. Dawson (Psychopharmacology, 2007)

Identification and imaging of soil and soil-pile deformation in the presence of liquefaction - M. Zeghal; P. V. Kallou; C. Oskay; T. Abdoun; M. K. Sharp (Earthquake Engineering and Engineering Vibration, 2006)

Development and genetic mapping of sequence-tagged microsatellites (STMs) in bread wheat (Triticum aestivum L.) - M. J. Hayden; P. Stephenson; A. M. Logojan; D. Khatkar; C. Rogers; J. Elsden; R. M. D. Koebner; J. W. Snape; P. J. Sharp (Theoretical and Applied Genetics, 2006)

Aromatase inhibition abolishes courtship behaviours in the ring dove (Streptopelia risoria) and reduces androgen and progesterone receptors in the hypothalamus and anterior pituitary gland - M. D. C. Belle; P. J. Sharp; R. W. Lea (Molecular and Cellular Biochemistry, 2005)

Differential involvement of serotonin and dopamine systems in cost-benefit decisions about delay or effort - F. Denk; M. E. Walton; K. A. Jennings; T. Sharp; M. F. S. Rushworth; D. M. Bannerman (Psychopharmacology, 2005)

Nuclear BAG-1 expression inhibits apoptosis in colorectal adenoma-derived epithelial cells - J. D. Barnes; N. J. Arhel; S. S. Lee; A. Sharp; M. Al-Okail; G. Packham; A. Hague; C. Paraskeva; A. C. Williams (Apoptosis, 2005)

Molecular structure of a novel y-type HMW glutenin subunit gene present in Triticum tauschii - M. E. Hassani; M. C. Gianibelli; M. R. Shariflou; P. J. Sharp (Euphytica, 2005)

Isotopic ( 13 C and 14 C) evidence supporting the transformative effect of cattle on north Australian vegetation - D. M. J. S. Bowman; B. R. Sharp; U. Zoppi (Journal of Biogeography, 2004)

A new approach to extending the wheat marker pool by anchored PCR amplification of compound SSRs - M. J. Hayden; P. Stephenson; A. M. Logojan; D. Khatkar; C. Rogers; R. M. D. Koebner; J. W. Snape; P. J. Sharp (Theoretical and Applied Genetics, 2004)

Construction and characterisation of a hexaploid wheat (Triticum aestivum L.) BAC library from the reference germplasm ‘Chinese Spring’ - S. Allouis; G. Moore; A. Bellec; R. Sharp; P. Faivre Rampant; K. Mortimer; S. Pateyron; T. N. Foote; S. Griffiths; M. Caboche; B. Chalhoub (Cereal Research Communications, 2003)

Methods of Compliance Evaluation for Ocean Outfall Design and Analysis - Not Available Not Available; L. M. LYE; J. J. SHARP (Environmental Management, 2002)

Correlation between extent of osteolytic damage and metastatic burden of human breast cancer metastasis in nude mice: Real-time PCR quantitation - Angus M. Tester; Julie A. Sharp; Nirada Dhanesuan; Mark Waltham; Erik W. Thompson (Clinical & Experimental Metastasis, 2002)

Genetic mapping of 66 new microsatellite (SSR) loci in bread wheat - P. Gupta; H. Balyan; K. Edwards; P. Isaac; V. Korzun; M. Röder; M.–F. Gautier; P. Joudrier; A. Schlatter; J. Dubcovsky; R. De la Pena; M. Khairallah; et al. (Theoretical and Applied Genetics, 2002)

Numerical Simulation of the Influence of Gravity and Posture on Cardiac Performance - Kristy Peterson; Edwin T. Ozawa; George M. Pantalos; M. Keith Sharp (Annals of Biomedical Engineering, 2002)

Insights into Wilson's Warbler migration from analyses of hydrogen stable-isotope ratios - Jeffrey F. Kelly; Viorel Atudorei; Zachary D. Sharp; Deborah M. Finch (Oecologia, 2002)

FURTHER CHARACTERIZATION OF BC3H1 MYOGENIC CELLS REVEALS LACK OF P53 ACTIVITY AND UNDEREXPRESSION OF SEVERAL P53 REGULATED AND EXTRACELLULAR MATRIX–ASSOCIATED GENE PRODUCTS - SANDRA B. SHARP; MARIA VILLALVAZO; MICKEY HUANG; RODOLFO GONZALEZ; IRANIA ALARCON; MATTHEW BAHAMONDE; DIANE M. D'AGOSTIN; SAGAR DAMLE; ALEX ESPINOSA; SEOG J. HAN; JESSICA LIU; PAULA NAVARRO; et al. (In Vitro Cellular & Developmental Biology - Animal, 2002)

Fluxes of semivolatile organochlorine compounds in Bow Lake, a high‐altitude, glacier‐fed, subalpine lake in the Canadian Rocky Mountains - Jules M. Blais; David W. Schindler; Martin Sharp; Eric Braekevelt; Melissa Lafreniěre; Karen McDonald; Derek C. G. Muir; William M. J. Strachan (Limnology and Oceanography, 2001)
The fluxes of several organochlorine compounds (OCs) to and from a high‐altitude lake were calculated to determine the relative contributions of rainfall, snowfall, runoff, gas absorption and volatilization, sedimentation, and outflow. Runoff inputs, particularly from a glaciated catchment, and gas absorption were major sources of many OCs. Losses by volatilization, outflow, and sedimentation were also important transport pathways for most OCs. We observed a net deposition of hexachlorocyclohexanes (HCHs) and DDT to Bow Lake by gas exchange, whereas hexachlorobenzene, chlordanes, and most polychlorinated biphenyls were seen to volatilize to the air. The insecticide lindane (γHCH), widely applied across Canada as a seed dressing in early spring, was absorbed by Bow Lake in early summer but gradually equilibrated with water as the summer progressed. This was the result of lower concentrations of γHCH in air and rising air temperatures in late summer. Results indicate that glacially derived tributary inputs are dominant sources of persistent organic pollutants to these glacier‐fed mountain lakes and that smaller contributions may derive from air‐water gas exchange. This study highlights the importance of glacial sources of OCs to mountain lakes and corroborates recent evidence of OC contamination in glacially derived aquatic systems.

Poster Session - J. van S. Graver; H. J. Banks; A. K. Sharp; A. Contessi; N. Baldassari; M. Maggioli; Sabine Prozell; Ch. Reichmuth; Maria Otília Carvalho; Ana Paula Pereira; A. Mexia; Sylvia Allen; et al. (Phytoparasitica, 2001)

Chromosome aberrations in wheat nullisomic-tetrasomic and ditelosomic lines - K. M. Devos; M. E. Sorrells; J. A. Anderson; T. E. Miller; S. M. Reader; A. J. Lukaszewski; J. Dubcovsky; P. J. Sharp; J. Faris; M. D. Gale (Cereal Research Communications, 1999)

Modulation of the malignant phenotype of human prostate cancer cells by N-(4-hydroxyphenyl)retinamide (4-HPR) - Mukta M. Webber; Diana Bello-DeOcampo; Salmaan Quader; Nestor D. Deocampo; W. Scott Metcalfe; Rebekah M. Sharp (Clinical & Experimental Metastasis, 1999)

Effect of antidepressant drugs on dopamine D 1 and D 2 receptor expression and dopamine release in the nucleus accumbens of the rat - K. Ainsworth; S. E. Smith; T. S. C. Zetterström; Q. Pei; M. Franklin; T. Sharp (Psychopharmacology, 1998)

Influence of Gravity on Cardiac Performance - George M. Pantalos; M. Keith Sharp; Stewart J. Woodruff; D. Sean O’Leary; Richard Lorange; Scott D. Everett; Thomas E. Bennett; Thomas Shurfranz (Annals of Biomedical Engineering, 1998)

Scaling of Hemolysis in Needles and Catheters - M. Keith Sharp; S. Fazal Mohammad (Annals of Biomedical Engineering, 1998)

The effect of infusion of hypertonic saline on glomerular filtration rate and arginine vasotocin, prolactin and aldosterone in the domestic chicken - A. M. Leary; J. R. Roberts; P. J. Sharp (Journal of Comparative Physiology B, 1998)

Gender comparison of peak oxygen uptake: repetitive box lifting versus treadmill running - Bradley C. Nindl; Marilyn A. Sharp; Robert P. Mello; Valerie J. Rice; Michelle M. Murphy; John F. Patton (European Journal of Applied Physiology, 1997)

Self-administration in rats allowed unlimited access to nicotine - James D. Valentine; Jonathan S. Hokanson; Shannon G. Matta; B. M. Sharp (Psychopharmacology, 1997)

Shear-augmented dispersion in non-Newtonian fluids - M. Keith Sharp (Annals of Biomedical Engineering, 1993)

Monoclonal antibodies for the identification of herpesvirus simiae (B virus) - L. M. Cropper; D. N. Lees; R. Patt; I. R. Sharp; D. Brown (Archives of Virology, 1992)

The ribosomal DNA transcription unit of the house cricket,Acheta domesticus - Jerry L. Ware; Z. Dave Sharp; M. Donald Cave (Biochemical Genetics, 1987)

A novel method for regenerating the protoplasts of thermophilic bacilli - R. M. Dunn; M. J. Munster; R. J. Sharp; B. N. Dancer (Archives of Microbiology, 1987)

Analysis of a large nontranscribed spacer in the ribosomal DNA of the house cricket,Acheta domesticus (Orthoptera:Gryllidae) - Z. Dave Sharp; Anna Meriwether; Jerry Ware; M. Donald Cave (Biochemical Genetics, 1986)

Infection of specific-pathogen free lambs with a herpesvirus isolated from pulmonary adenomatosis - F. M. M. Scott; J. M. Sharp; K. W. Angus; E. W. Gray (Archives of Virology, 1984)

Rapid transmission of sheep pulmonary adenomatosis (jaagsiekte) in young lambs - J. M. Sharp; K. W. Angus; E. W. Gray; F. M. M. Scott (Archives of Virology, 1983)